A Statistical Trend Of The Development Of Android Islamic Apps In Malaysia From 2000 To 2017 - Mohd Zabidi, Muhammad Izzat Zakwan; Zakaria, Syamimi; Zainal Abidin, Amar Faiz; Hasim, Nur Aiman Hanis; Azahar, Arman Hadi; Harun, Mohd Hanif (World Academy of Research in Science and Engineering, 2020)
This paper presents the statistical trend related to the Android-based Islamic apps published in Malaysia's Google App Store from the year 2000 to 2017. The statistical analysis based on seven point-of-view: 1) category; 2) year; 3) country; 4) price; 5) total download; 6) keyword. This statistical trend analysis aims to give insight for the Android App Developer on the current trend of the Islamic apps published in Malaysia Google App Store.